METODE PEMBELAJARAN DAN SISTEM REGENERASI DALAM ORKES KERONCONG KAKAS DI KABUPATEN TRENGGALEK: metode pembelajaran, sistem regenerasi, musik keroncong, pendidikan nonformal, orkes keroncong KAKAS - Arya Lubbis; Tomy Sugito (Universitas Negeri Surabaya, 2025)
This study aimed to describe the learning methods of keroncong music and the musician regeneration system implemented in Orkes Keroncong KAKAS, Trenggalek Regency. This study employed a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation, and analyzed using the Miles, Huberman, and Saldaña model, which consists of data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The findings revealed that the learning process in Orkes Keroncong KAKAS is conducted within a nonformal education setting through demonstration, repetitive practice, peer tutoring, ensemble practice, and a fun learning approach supported by reinforcement. The regeneration system is carried out through the recruitment of new members from schools, mentoring by senior members, active participation in rehearsals and performances, and the transmission of musical knowledge, skills, cultural values, and musical identity to younger generations. The study concludes that the learning methods and regeneration system in Orkes Keroncong KAKAS complement each other in developing musical competence while sustaining keroncong music through a continuous process of cultural transmission.